Optimization of a High-Protein and High-Fiber Gluten-Free Cookies Formula Based on Composite Flour - Endah Wulandari; Debby Sumanti Moody; Aldila Pangawikan; Dzakiyah Assyafiqah (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
Cookies are widely consumed snacks with wheat flour as the main ingredient. However, due to their wheat content, the snacks cannot be consumed by people with gluten intolerance or celiac disease. This indicates that there is a need for innovative gluten-free cookies with rich nutritional content, such as the use of composite flour. Several studies have shown that composite flour consists of rice, bran, and moringa leaf flours. Therefore, this study aims to determine the optimal formula for composite flour in cookies with acceptable organoleptic and physicochemical characteristics. The study procedures were carried out using Response Surface Methodology (RSM) with Central Composite Design (CCD). The recommended optimal formula consisted of 22.57% rice, 21.22% bran, and 2.26% moringa leaf flours. In terms of nutrients, it contained 10.41% protein, 1.99% fiber, 5.99% moisture, 3.08% ash, 21.76% fat, and 58.76% carbohydrates. Physicochemical analysis results showed that the cookies had a yellowred color, a hard-brittle texture, 5.99% moisture, 3.08% ash, 21.76% fat, and 58.76% carbohydrate. The sensory evaluation showed that the products obtained had a brownish-green color, a slightly musty aroma, a hard texture, a strong bitter taste, a strong aftertaste, and a neutral overall appearance. Based on these results, the cookies had physicochemical and organoleptic characteristics that were moderately tolerable to the panelists.